AN INTEGRATED STUDY PACK BASED ON A SHORT FILM ENTITLED “SLAP HER: CHILDREN’S REACTION” - Noor Aeni (Universitas Ahmad Dahlan)
This study aims to develop a set of alternative English teaching and learning materials covering four language skills (listening, speaking, reading, and writing). Learning materials are designed based on a short film entitled “Slap her: Children’s Reaction”. It is designed for language teachers of general English course for adult learners of English as a foreign language with the proficiency level of B2 according to CEFR (the Common European Framework of Reference for Languages).The nature of the study is Research and Development (R & D). The involving steps are conducting needs analysis, designing the course grid, and developing the materials. Data were collected by analyzing CEFR documets and conducting interview. They were analyzed quantitatively and qualitatively.The activities within the study pack were designed in chronological order. They are categorized in three orders, before viewing the short film “Slap her”: children’s reactions, during, and after the viewing. The activities are interlinked on levels B2 of CEFR. The activities content builds logically onto each other, with later activities that are recycling language items or content of previous activities. The activities involve all four language skills that are integrated. In the implementation of the study pack, students will be required to work either, individually, in pairs, even in groups.